Pengaruh K3 (Keselamatan dan Kesehatan Kerja), Beban Kerja dan Kompensasi Terhadap Produktivitas Karyawan: Studi pada PT. Cahaya Karya Bersama Mojokerto - Voni Apriliasari; Rini Armin; Kasnowo Kasnowo (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to examine the influence of Occupational Health and Safety (OHS), workload, and compensation on employee productivity at PT Cahaya Karya Bersama. The background of this research lies in the importance of human resource management in enhancing company performance amid intense business competition. Despite the company’s efforts in providing safety facilities and implementing OHS systems, issues still arise such as low employee awareness of safety procedures, unequal workload distribution, and dissatisfaction with compensation systems, particularly in relation to BPJS Health services. This study employs a quantitative approach by distributing questionnaires to 40 respondents via Google Form, with data analyzed using SPSS 25. The results indicate that partially, OHS, workload, and compensation variables have a significant effect on employee productivity. Furthermore, these three variables also jointly contribute significantly to productivity enhancement. Therefore, the company must further optimize OHS implementation, ensure workload alignment with employee capacity, and improve its compensation system to create a productive and sustainable work environment.